Matching biodiversity indicators to policy needs - Stevenson, Simone L.; Watermeyer, Kate; Caggiano, Giovanni; Fulton, Elizabeth A.; Ferrier, Simon; Nicholson, Emily (Conservation biology, 2021)
At the global scale, biodiversity indicators are typically used to monitor general trends, but are rarely implemented with specific purpose or linked directly to decision making. Some indicators are better suited to predicting future change, others are more appropriate for evaluating past actions, but this is seldom made explicit. We developed a conceptual model for assigning biodiversity indicators to appropriate functions based on a common approach used in economics. Using the model, indicators can be classified as leading (indicators that change before the subject of interest, informing preventative actions), coincident (indicators that measure the subject of interest), or lagging (indicators that change after the subject of interest has changed and thus can be used to evaluate past actions). We classified indicators based on ecological theory on biodiversity response times and management objectives in 2 case studies: global species extinction and marine ecosystem collapse. For global species extinctions, indicators of abundance (e.g., the Living Planet Index or biodiversity intactness index) were most likely to respond first, as leading indicators that inform preventative action, while extinction indicators were expected to respond slowly, acting as lagging indicators flagging the need for evaluation. For marine ecosystem collapse, indicators of direct responses to fishing were expected to be leading, while those measuring ecosystem collapse could be lagging. Classification defines an active role for indicators within the policy cycle, creates an explicit link to preventative decision‐making, and supports preventative action. Alineamiento entre los Indicadores de Biodiversidad y los Requerimientos Políticos Resumen En la escala global, los indicadores de biodiversidad se usan comúnmente para monitorear las tendencias generales pero rara vez se implementan con un propósito específico o vinculados directamente con la toma de decisiones. Algunos indicadores son mejores para predecir los cambios futuros, mientras que otros son más apropiados para la evaluación de acciones pasadas, aunque lo anterior casi nunca se comunica explícitamente. Desarrollamos un modelo conceptual para la atribución de indicadores de biodiversidad a funciones apropiadas con base en una estrategia común que se usa en la economía. Con este modelo, los indicadores pueden clasificarse como principales (indicadores que cambian antes que el sujeto de interés, orientando así las acciones preventivas), coincidentes (indicadores que miden al sujeto de interés) o rezagados (indicadores que cambian después de que el sujeto de interés ha cambiado y por lo tanto puede usarse para evaluar las acciones pasadas). Clasificamos los indicadores con base en la teoría ecológica sobre los tiempos de respuesta de la biodiversidad y los objetivos de manejo en dos estudios de caso: la extinción mundial de especies y el colapso de los ecosistemas marinos. Para la extinción mundial de especies, los indicadores de abundancia (p. ej.: el Índice del Planeta Viviente o el índice de biodiversidad intacta) fueron los más probables en tener una respuesta pronta como indicadores principales que orientan las acciones preventivas, mientras que se esperó que los indicadores de extinción tuvieran respuestas lentas, por lo que actuarían como indicadores rezagados que disminuyeron la necesidad de evaluación. Para el colapso de los ecosistemas marinos, se anticipó que los indicadores de las respuestas directas a la pesca fueran los indicadores principales, mientras que aquellos que miden el colapso del ecosistema podrían ser indicadores rezagados. La clasificación define un papel activo para los indicadores dentro del ciclo de políticas, crea un vínculo explícito con la toma de decisiones preventivas y respalda la acción preventiva. 摘要 在全球范围内, 生物多样性指标常常用于监测整体趋势, 但很少有具体实施目的或直接与决策挂钩。有些指标更适合预测未来的变化, 有些指标则更适合评价过去的行动, 但这一点很少得到说明。基于经济学中的常用方法, 我们开发了一个根据恰当功能分配生物多样性指标的概念模型。该模型将指标分为领先指标 (先于研究主体发生变化的指标, 可为预防性行动提供信息) 、同步指标 (度量研究主体的指标) 及滞后指标 (研究主体变化后才发生变化的指标, 可用于评估过去的行动) 。我们以全球物种灭绝和海洋生态系统崩溃作为案例, 根据生物多样性响应时间的生态学理论和管理目标对相应指标进行了分类。在全球物种灭绝的案例中, 种群数量指标 (如地球生命力指数或生物多样性完整性指数) 最有可能首先产生响应, 它们是可以为预防行动提供信息的领先指标, 而灭绝相关的指标预期响应缓慢, 则是表明评估需求的滞后指标。对于海洋生态系统崩溃而言, 衡量对渔业直接响应的指标应为领先指标, 而生态系统崩溃的相关指标可能为滞后指标。对指标的分类确定了其在政策周期中的积极作用, 建立了指标与预防性决策的明确联系, 并支持了预防性行动。【翻译: 胡怡思; 审校: 聂永刚】 Article Impact Statement: Some biodiversity indicators are best suited to prediction for preventative action and others to retrospection and evaluating past actions.